PENGARUH PENGGUNAAN MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBER HEAD TOGETHER DENGAN PENDEKATAN BERBASIS MASALAH TERHADAP KEMAMPUAN SISWA DALAM PEMECAHAN MASALAH PERBANDINGAN - Wamington . Rajagukguk (INSPIRATIF : JURNAL PENDIDIKAN MATEMATIKA, 2016)
ABSTRACTThe main problem of this study was the lack of ability in problem solving of junior high school (SMP) students about Comparison. To improve this ability, it was used the cooperative learning model of Number Head Together (NHT) type with approaching of problem based learning. The problem formulations would be studied in this study namely: Whether the cooperative learning model of NHT type with approaching of problem based learning influenced the students' skills in problem solving of comparison lesson. For the purposes of this study were to: (1) describe the implementation of cooperative learning model of NHT type with approaching of problem based learning; (2) describe an improvement in problem solving ability of students in comparison taught by using cooperative learning model of NHT type and approaching of problem based learning. Design of this study was two-group pretest-posttest design. The population was all students of class VII SUMBUL. Ability of mathematical problem solving of students was measured by using test of ability of problem solving. But looking for quality of the improvement obtained from two groups was conducted by testing on the index gain. The result of study showed that the ability of mathematical problem solving between students who were taught by using cooperative learning model of NHT type with approaching of problem based learning was higher than students who were taught just by problem based learning. It showed that there was the influence of cooperative learning model of NHT type with approaching of problem based learning to ability of mathematical problem solving. Based on the result of this study, it was suggested that teachers taught the mathematical problem solving by using cooperative learning model of NHT type with approaching of problem based learning.Key Words: Cooperative Learning Model of NHT Type; Approaching of Problem Based Learning; Ability of Problem Solving.